A novel hybrid termination structure for vertical gallium nitride Schottky barrier diode by using technology computer aided design simulation - Jian Li (Wiley, 2021)
Abstract Gallium nitride based high‐power electronic devices are now in full swing. However, the phenomenon that the gallium nitride Schottky diodes break down prematurely without reaching the gallium nitride material limit is unsolved. This paper proposes a novel hybrid termination structure for vertical gallium nitride Schottky diodes to improve breakdown voltage. This work is carried out to simulate the breakdown voltage and reverse characteristics of the vertical gallium nitride Schottky diode by using technology computer aided design (TCAD) simulation. Under the same testing conditions, we demonstrate that compared with the control vertical Schottky diode, the breakdown voltage of the proposed Schottky diode can be significantly advanced, which has increased by 350 V and reached 850 V.